Unusual localization of Pennella sp. in swordfish (Xiphias gladius) hearts. - Mugetti, D., E. Colombino, V. Menconi, F. Garibaldi, W. Mignone, A. Gustinelli, M. Prearo, F. Guarda & M.T. Capucchio (Animals, 2021)
Copepods of the genus Pennella are parasites of marine aquatic organisms (e.g., cephalopods, pelagic fish, cetaceans). They can infest fish of economic interest, including tuna and swordfish. The infestation of Pennella sp. in fish creates problems of food safety and fish marketing. Generally, these copepods penetrate the host’s muscle, without damaging internal organs. Here, we report on Pennella sp. infestation in swordfish heart muscle. The severity of the cardiac lesions we observed suggests that parasites of the genus Pennella pose a concern for food safety as well as animal health.